Analisis Infrastruktur TI Lapak Aduan Banyumas Diskominfo Kabupaten Banyumas Menggunakan SWOT dan Value Chain untuk Evaluasi Layanan Publik - Nesa Nur Puspitasari; Nur holifah, Anggita; Retno Setioningrum; Putri Nazilatus Safa’at; Ito Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to explore the condition of information technology infrastructure and to evaluate the extent to which the Lapak Aduan Banyumas service, managed by the Department of Communication and Informatics of Banyumas Regency, operates effectively. The study employs SWOT and Value Chain analysis approaches. A qualitative descriptive method is applied, with data collected through interviews and documentation involving officers responsible for managing the service. The results indicate that Lapak Aduan Banyumas has been operating optimally as a digital-based, transparent, and effective public complaint channel. Its main strengths lie in the ease of access through multiple service channels and the availability of features that enable real-time complaint status tracking. However, several challenges remain, including a limited number of human resources, less optimal collaboration among regional government organizations (OPDs), and network infrastructure constraints in several areas. The Value Chain analysis reveals that the complaint follow-up process and the dissemination of handling outcomes to the public represent the stages that generate the greatest added value in the service process. Therefore, this study suggests strengthening the complaint status monitoring system, enhancing inter-platform service integration, and utilizing artificial intelligence technologies to improve the complaint handling process. The findings of this study are expected to serve as a strategic basis for improving the quality of digital public services in Banyumas Regency.